The Integration of Aswaja NU Values and Kohlberg's Theory as the Foundation of Early Childhood Moral Education in Indonesia: A Conceptual Study - Leksana, Dinar Mahdalena Leksana; Naqiyah, Najlatun; Khusumadewi, Ari; Kurniawan, Shopyan Jepri (Jurnal Pendidikan Karakter, 2025)
This article synthesizes the theory of moral development according to Lawrence Kohlberg with the values of Aswaja NU and the practice of guidance-counseling (BK) as a conceptual model of early childhood moral education in Indonesia. The purpose of the paper is to formulate an integrative framework that combines moral rationality (Kohlberg) with the spiritual-cultural dimension of Aswaja NU through the medium of implementing BK services in PAUD and elementary schools. The method used is a systematic review based on PRISMA 2015–2025 on reputable databases, followed by screening, quality assessment, and content analysis with thematic coding of 35 journal articles and 5 relevant book chapters. The results show: (1) the child's preconventional stage becomes the foundation of moral reasoning that needs to be stimulated through social-reflective experiences; (2) Aswaja values (tawassuth, tawazun, tasamuh, i'tidal, amar ma'ruf nahi munkar, rahmah) complement the individualistic-secular bias in the Kohlberg framework; (3) classical, group, and individual BK services are effective in internalizing values through dialogue, example, habituation, and behavior reinforcement. Conclusion: Kohlberg-Aswaja-BK integration produces a holistic, contextual, and applicative "Aswaja-Based Moral Counseling" model that is holistic, contextual, and applicative to strengthen character education and religious moderation in early childhood in Indonesia.